Divergent skeletal muscle mitochondrial phenotype between male and female patients with chronic heart failure. Issue 1 (20th August 2019) - Garnham, Jack O.; Roberts, Lee D.; Caspi, Talia; Al‐Owais, Moza M.; Bullock, Max; Swoboda, Peter P.; Koshy, Aaron; Gierula, John; Paton, Maria F.; Cubbon, Richard M.; Kearney, Mark T.; Bowen, T. Scott; et al.
Abstract: Background: Previous studies in heart failure with reduced ejection fraction (HFrEF) suggest that skeletal muscle mitochondrial impairments are associated with exercise intolerance in men. However, the nature of this relationship in female patients remains to be elucidated. This study aimed to determine the relationship between skeletal muscle mitochondrial impairments and exercise intolerance in male and female patients with HFrEF. Methods: Mitochondrial respiration, enzyme activity, and gene expression were examined in pectoralis major biopsies from age‐matched male ( n = 45) and female ( n = 11) patients with HFrEF and healthy‐matched male ( n = 24) and female ( n = 11) controls. Mitochondrial variables were compared between sex and related to peak exercise capacity. Results: Compared with sex‐matched controls, complex I mitochondrial oxygen flux was 17% ( P = 0.030) and 29% ( P = 0.013) lower in male and female patients with HFrEF, respectively, which correlated to exercise capacity ( r = 0.71; P > 0.0001). Female HFrEF patients had a 32% ( P = 0.023) lower mitochondrial content compared with controls. However, after adjusting for mitochondrial content, male patients demonstrated lower complex I function by 15% ( P = 0.030). Expression of key mitochondrial genes regulating organelle dynamics and maintenance (i.e. optic atrophy 1, peroxisome proliferator‐activated receptor γ coactivator‐1α, NADH:ubiquinone oxidoreductase core subunit S1/S3, and superoxide dismutase 2) were selectively lower in female HFrEF patients. Conclusions: These data provide novel evidence that HFrEF induces divergent sex‐specific mitochondrial phenotypes in skeletal muscle that predispose towards exercise intolerance, impacting mitochondrial 'quantity' in female patients and mitochondrial 'quality' in male patients. Therapeutic strategies to improve exercise tolerance in HFrEF should consider targeting sex‐specific mitochondrial abnormalities in skeletal muscle.